Development of the National Education Curriculum from the Old Order Era to the Reform and Decentralization Era (1947-2022): Perkembangan Kurikulum Pendidikan Nasional Era Orde Lama Hingga Era Reformasi dan Desentralisasi (1947-2022) - Ahmad Basyori; Aan Budianto3c; Fariq Syah Putra (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2026)
This research, entitled "The Development of the National Education Curriculum from the Old Order Era to the Reform and Decentralization Era (1947–2022)," is motivated by the importance of the curriculum as a strategic instrument in determining the direction, content, and quality of national education. The curriculum serves not only as a technical guide for learning but also as an ideological, social, and political tool for shaping the nation's character in accordance with the dynamics of the times. The purpose of this research is to analyze the development and changes in the Indonesian national education curriculum from the Old Order era, the New Order era, to the Reform and Decentralization era. The research method used is historical, with four stages: heuristics, source criticism, interpretation, and historiography. The results show that during the Old Order era (1947–1965), the curriculum was oriented towards the formation of national character and the strengthening of national identity through the 1947 Lesson Plan, the 1952 Detailed Lesson Plan, and the 1964 Curriculum, which emphasized the Pancawardhana concept. During the New Order era (1968–1998), the curriculum became a tool for centralistic state ideological control, as reflected in the 1968, 1975, 1984, and 1994 Curricula which focused on political stability and Pancasila values. Entering the Reformation and Decentralization era (2004–2022), the direction of education policy shifted toward a decentralized and competency-based paradigm. The Competency-Based Curriculum (2004), the KTSP (School-Based Curriculum) (2006), the 2013 Curriculum, the Emergency Curriculum (2020–2021), and the Independent Curriculum (2022) .